HUBUNGAN PENGETAHUAN TENTANG KARIES GIGI DENGAN MOTIVASI UNTUK MELAKUKAN PENAMBALAN GIGI PADA IBU RUMAH TANGGA - Sinaga, Anjela Br; Khasanah, Furaida; Suyatmi, Dwi (Journal of Oral Health Care, 2021)
Caries is a disease dental infections that exist in the oral cavity that is often found in people age young, mature and old so that if not treated can cause pain that may potentially lead to tooth loss. Based on the results of a preliminary study conducted for only 2% of housewives who come to the health service to do fillings because of its own accord, the results of preliminary studies indicate the lack of knowledge about dental caries will affect the motivation of someone doing a dental filling. The purpose of this study knowing the relationship of knowledge about dental caries with the motivation to do fillings in housewives. This type of research is analytic survey with survey design cross-sectional population housewife age range 35 – 44 years. Sample research used total sampling method with data collection technique using purposive sampling. Data collection using a questionnaire. The result showed the average of respondents knowledgeable high (55%) and have the motivation is low (45%). The data analysis in this research using the test provided by kendall's Tau-b with hypothesis testing based on the significance level ? <0.05 with a confidence level of 95%. Known significant value ? = 0,003, ? < 0.05 with a coefficient of correlation = 0,436. The conclusion of study is knowledge about dental caries were significantly related to motivation to do fillings